Improving the Grain Distribution System in the Context of the State Regulation of the Market - STADNIK, Anatoly T.; CHERNOVA, Svetlana G.; VAHNEVICH, Konstantin E.; SCHELKOVNIKOV, Sergei; SAMOKHVALOVA, Anastasia A.; LEONOVA, Yana V. (Journal of Advanced Research in Law and Economics; Vol 10 No 3 (2019): JARLE Vol X Issue 3(41) Summer 2019, 2019)
The grain farming is the basic sector of the agro-industrial complex (AIC) of the Russian Federation, which has always been the basis for the sustainable development of the entire agricultural sector of the country. The feed grain is of particular importance for obtaining cheap livestock products and import substitution in this field. The share of the imported meat and dairy products will sharply decrease if the system of ensuring self-sufficiency for the country's regions with grain is properly built. At the same time, the resources spent on imports will fund the development of the entire AIC. Due to some natural and economic factors, not all regions in the Russian Federation are able to provide themselves with their own grain. It is favorable for such regions to import cheap grain from other regions and to supply their cheap livestock products to these regions. Most of the grain should be fed to livestock and poultry in order to eliminate the discrepancy between the export and import of food. The attempts are made in the Russian Federation to transfer agriculture to an industrial basis, but, unfortunately, this is done only in the farms that receive high subsidies and preferential loans, while most of the farms try to develop at their own expense, which they lack. This results in the technological backwardness of the industry and the general crisis state.